Impact of Social Media in Workplace in Commercial Bank in Nepal - Bahety, Harshika (Nepalese Journal of Management, 2025)
This study examines the factors influencing workplace environment in Nepalese commercial banks. Workplace environment is selected as the dependable variable. Similarly social media, trust, privacy, compatibility, perceived ease of use and cost are selected as the independent variable. The primary source of data is used to assess the opinions of the respondents regarding the factors influencing workplace environment in Nepalese commercial banks. The study is based on primary data of 153 respondents from 17 commercial banks of Nepal. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and different factors influencing employee retention in Nepalese insurance companies. The study showed that social media has a positive impact on workplace environment. It indicates that increase in use of social media leads to increase in impact in workplace environment. Likewise, trust has a positive impact on workplace environment. It indicates that increase in trust leads to increase in impact in workplace environment. Similarly, privacy has a positive impact on workplace environment. It means that privacy leads to increase in impact in workplace environment. Moreover, compatibility has a positive impact on workplace environment. It indicates that better the compatibility, higher would it impact the workplace environment. In addition, perceived ease of use has a positive impact on workplace environment. It reveals that perceived ease of use leads to increase in impact in workplace environment. The result also reveals that cost has a positive impact on workplace environment. It implies that maintaining lower cost leads to increase in impact in workplace environment.